Decomposed chicken feather: A biostimulant to lettuce (Lactuca sativa) growth - AHMADI, LEILI; BAHARLOUEI, JILA; KHAVAZI, KAZEM; DAVOUDI, MOHAMMAD HOSSEIN (The Indian Journal of Agricultural Sciences, 2024)
It is crucial to produce plant growth biostimulants from waste and renewable resources. A study was carried during 2020 at the Soil and Water Research Institute, Karaj, Iran to evaluate the effect of decomposed chicken feather as a biostimulant on lettuce (Lactuca sativa L.) growth. A total of 29 soil samples from 15 Iranian regions were used to isolate and identify the bacteria and 31 strains that were able to produce keratinase and capable of feather degrading were isolated. Then, 8 isolates that were able to degrade the feather during 7 days were selected as the superior strains. Based on the results Bacillus siamensis c11, Bacillus methylotrophicus gh1 and Bacillus methylotrophicus a2 were identified as the new strains that can produce keratinase enzyme. Then, the effect of foliar spraying of the solutions produced from feather degradation by the new strains (c11, gh1, and a2) on the growth of lettuce was investigated. The results showed that the solution produced by methylotrophicus gh1 strain significantly increased the fresh and dry weight of the shoot and root (respectively, 25.9, 36.9, 34.1 and 51.9% increase compared to the control). It is concluded that the microbial solution of these three microbes as a consortium could be quite a new addition on one hand, could also reduce the human allergy as a via- medium of waste disposal.